Considerações acerca da Educação de Jovens e Adultos - Santos, Gabriela Letícia M. dos (Universidade Federal do Tocantins, 2022)
The present study is the conclusion monograph of the Pedagogy Course. Your main objective was to carry out readings and reflections about the Education of Young People and Adults. From the methodological point of view, a qualitative research was carried out, bibliographic character, supported by authors who debate the theme and organized in three sections. Youth and Adult Education is a teaching modality aimed at young people and adults who have not had access or who for some reason cannot were able to complete their education at the proper age. It is offered to young people from the age of 15 of age, by Organs responsible bodies, in person or at a distance. We understand that EJA – youth and adult education has many challenges, mainly because it is an alternative to minimize the problem of social exclusion. It is important in working with EJA to think about education as a cultural phenomenon, of paramount importance in the formation of the educational process, because, as we know, without culture there is no education. Through society, culture manifests itself as a means of reproduction of culture.